Strategic management of agricultural and life sciences research - Heimann, Bettina; O'Brien, Lance (éditions Quae, 2019)
New developments - scientific, technical, societal and political - influence not only the agenda for research but also research structures, resource requirements (human and otherwise), education and training programs and interfaces with partners and the users of research. They also have an impact on research funding and management and the way research is evaluated and monitored. This book deals with the business of doing research in Europe's public research and development organisations, with a particular focus on their strategic management challenges. It is the third e-book produced by EURAGRI and draws on contributions made at the 31st EURAGRI annual conference held in Dublin (Ireland) in September 2017.